Harmonic Analysis of Seven and Nine Level Cascade Multilevel Inverter using Multi-Carrier PWM Technique - Chetanya Gupta; Devbrat Kuanr; Abhishek Varshney; Tahir Khurshaid; Kapil Dev Singh (Institute of Advanced Engineering and Science, 2014)
The use of multilevel inverters has become popular in recent years for high-power applications. Multilevel Inverters are power converter systems composed by an array of power semiconductor sources that when properly connected and controlled can generate a multistep voltage waveform with variable and controllable frequency, phase and amplitude. This study deals with the comparison of a 7-level inverter with a 9-level inverter system; the voltage source inverters (VSI) are modelled and simulated using MATLAB Simulink and the results are presented. The test results verify the effectiveness of the proposed strategy in terms of computational efficiency as well as the capability of the inverter to produce very low distorted voltage with low-switching losses. This research aims to extend the knowledge about the performance of different clamped multilevel inverter through harmonic analysis. Simulations results validate up to the mark performance of the mentioned topologies.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6190